MORAL MESSAGE IN SONG LYRICS AKU BUKAN JODOHNYA BY TRI SUAKA - Abid Nurhuda; Afiffah Vinda Prananingrum (Universitas Muhammadiyah Surakarta, 2022)
Communication is important so that humans can interact to create meaning and messages for individuals or groups. And in delivering messages, media can be used, one of which is a song consisting of music and lyrics because it is considered a proper and adequate medium to channel thoughts, hopes, or special and moral messages to the audience. Among the many songs that went viral in January 2022, Aku Bukan Jodohnya by Tri Suaka, so the purpose of this study was to describe the moral message contained in it. The method used is qualitative and the data is collected in a documentary manner accompanied by a note-taking technique then analyzed the contents and finally concludes. The results of the study indicate that the moral message in the song lyrics of Aku Bukan Jodohnya by Tri Suaka includes psychological messages such as sincerity, submission, and determination, then social criticism messages, namely doing good to people who hurt us, and finally religious messages, namely believing in destiny.